2018
DOI: 10.1186/s40409-018-0174-7
|View full text |Cite
|
Sign up to set email alerts
|

Second-generation pterocarpanquinones: synthesis and antileishmanial activity

Abstract: BackgroundDespite the development of new therapies for leishmaniasis, among the 200 countries or territories reporting to the WHO, 87 were identified as endemic for Tegumentary Leishmaniasis and 75 as endemic for Visceral Leishmaniasis. The identification of antileishmanial drug candidates is essential to fill the drug discovery pipeline for leishmaniasis. In the hit molecule LQB-118 selected, the first generation of pterocarpanquinones was effective and safe against experimental visceral and cutaneous leishma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Considering Colombia as a country with a significant number of pathogenic Leishmania species in circulation, these facts are very critical, bearing in mind that parasite sensitivity to antileishmanial agents relies on Leishmania species [70,71]. For instance, a study evaluated dehydroabietylamine derivatives and found species-dependent susceptibility for several of them [72], being consistent with other reports [73,74]. Indeed, owing to the role of intraand inter-species Leishmania susceptibility [71,75,76], the incorporation of drug-resistant strains during antileishmanial research programs have been strongly recommended [77].…”
Section: General Findingssupporting
confidence: 76%
“…Considering Colombia as a country with a significant number of pathogenic Leishmania species in circulation, these facts are very critical, bearing in mind that parasite sensitivity to antileishmanial agents relies on Leishmania species [70,71]. For instance, a study evaluated dehydroabietylamine derivatives and found species-dependent susceptibility for several of them [72], being consistent with other reports [73,74]. Indeed, owing to the role of intraand inter-species Leishmania susceptibility [71,75,76], the incorporation of drug-resistant strains during antileishmanial research programs have been strongly recommended [77].…”
Section: General Findingssupporting
confidence: 76%
“…High-throughput screening has been employed by several researchers either as phenotypic screens [32,102,121,122] or target-specific, such as Leishmania protein disulfide isomerase [40,123]. Several compound classes have been identified with potent antileishmanial activity, including substituted 1,2-dioxanes [124], mono-arylimidamides [125], pterocarpanquinones [126], C-10b-substituted dihydropyrrolo [1,2-b]isoquinolines [127], amino-substituted 1H-phenalen-1-ones [128], and chalcones [129]. For example, Ortalli et al (2018) synthesized 31 novel chalcone compounds, with 16 compounds showing activity against L. donovani promastigotes [129].…”
Section: Drug Discovery Targeting Multiple Species Of Leishmaniamentioning
confidence: 99%
“…The assays were performed in triplicate in 96-well plates (Costar, New York, United States). Inhibition parasite growth was assessed by a fluorescent assay, Resazurin (Sigma-Aldrich) (Faiões et al, 2018). Briefly, 50 µM of resazurin was added per well, and then the samples were incubated for an additional 2 h. The fluorescence was measured using a Spectra Max GEMINI XPS spectrofluorometer (Molecular Devices, Silicon Valley, United States) at excitation and emission wavelengths of 560 and 590 nm, respectively.…”
Section: Antipromastigote Activitymentioning
confidence: 99%